Univalence criteria and quasiconformal extensions - Çaǧlar, M.; Orhan, H. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We establish more general conditions for the univalence of analytic functions in the open unit disk $U$. In addition, we obtain a refinement to the criterion of quasiconformal extension for the main result.